Psychotherapy employed additionally to Psychopharmacotherapy is not related to Better Treatment Outcome in Major Depressive Disorder - L. Bartova; G. Fugger; M. Dold; M. Mitschek; J. Zohar; J. Mendlewicz; D. Souery; S. Montgomery; C. Fabbri; A. Serretti; S. Kasper (European Psychiatry, 2022)
Introduction Although numerous effective antidepressant (AD) strategies are available for the treatment of major depressive disorder (MDD), many patients do not achieve satisfactory treatment response.